Social Intervention and Governance of Youth School Bullying—Based on Computer Medical Data Analysis - Zhao, Jiahui (Frontiers in Public Health, 2022)
The rise of computational social science provides a new method for campus bullying research based on large-scale data collection, calculation and analysis.Governing the bullying behavior of a middle school through social intervention, and closely observe the service needs and existing problems of the school youth group. This paper analyzes the characteristics, inducements and negative effects of school bullying. Combine drama courses and working group education methods to intervene in school bullying. Intervention work includes making teenagers aware of bullying behavior and identifying bullying types. To achieve the purpose of empathy through role play, bullies can effectively control irrational thoughts, understand their own cognitive biases, and reconcile their own emotions and behaviors. So that the victims can identify the bullying behavior around them in time, and cultivate their resistance and self-protection awareness in the event of bullying. Based on the empirical analysis of social work to intervene in the practical dilemma, and put forward the corresponding countermeasures to reduce the negative impact of school bullying on all aspects of youth, so as to reduce the various social risks brought by school bullying.